1980
DOI: 10.1203/00006450-198006000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Protective Value of Gamma Globulin Preparations against Group B Streptococcal Infections in Chick Embryos and Mice

Abstract: SummaryI'he protective value of pooled human gamma globulin (GG) and a group B streptococcal immune globulin (GBSIG) was studied in a chick embryo and a murine model of group B streptococcal (GBS) infection. Chick embryos were protected by the I V administration of 0.4 to 0.8 mg of GG from three manufacturers against I V challenge with type l a GBS. Two of three G G preparations at doses of 0.4 to 1.65 mg protected chick embryos against type 111, but 1.65 mg of all three preparations failed to protect against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This demonstrated again a correlation between antibody levels and mouse protection. Most studies by others were concerned with the correlation between mouse protection and in vitro phagocytic assays (1 1, 12,13,29,34,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This demonstrated again a correlation between antibody levels and mouse protection. Most studies by others were concerned with the correlation between mouse protection and in vitro phagocytic assays (1 1, 12,13,29,34,38).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a number of studies have been published concerning the protective effect of gammaglobulin preparations in experimental GBS-infections. Three animal species have been used: chicken embryos (38), neonatal rats (1 1, 12, 29) and mice (3,13,34). Most interest has been focused on carbohydrate antigens, in particular type I11 antigen (3, 1 1, 12, 13,29), whereas few studies concerning types Ia, Ib and I1 have been reported (34,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously described animal models for GBS sepsis have included inoculation of bacteria into amniotic fluid (9) and directly into newborns (5,10,11) and have not included maternal infection. This animal model of vertical transmission can be used to study the mechanisms of transmission of GBS from mother to infant and to investigate regimens aimed at preventing earlyonset group B ~t r e~t o c~c c a l infection.…”
Section: Discussionmentioning
confidence: 99%
“…To delineate the role of growth hormone (GH) in the development and function of the immune system, immunological parameters including quantitative immunoglobulins, T and B lymphocytes, phytohemagglutinin lymphoproliferative response and delayed hypersensitivity skin tests were studied in nine GH-deficient children prior to GH therapy and at 2 months and 9 to 12 months following therapy. The phytohemagglutinin response (74.1 + 37.6, mean f SD), and the T rosette (58.3% GH plays a significant role in the normal development of thymic-dependent immune function in lower mammals (3,4,11,14). Although immune deficiency states in man are frequently associated with impaired growth, abnormalities of GH secretion has not been implicated in such conditions.…”
mentioning
confidence: 99%